Characterizing polycrystalline microstructures by reconstructing grain boundaries and velocity map from ultrasonic surface wave field - Sun, Zeqing (2024)
An ultrasonic material characterization method is proposed to reconstruct the polycrystalline microstructures from the field-measurement of ultrasonic surface waves. Two wavenumber-frequency domain filters are developed to extract specific wave components for the reconstructions. One is the evanescent-pass filter that can be used to reconstruct the grain boundaries. The other is the directional filter to map the surface wave velocity along a specific direction. The method is validated by numerical simulations, as well as by experiments, on an additively manufactured sample. Sub-wavelength resolution can be achieved by the proposed method if sufficient data is captured spatially within one wavelength of the surface wave.